THE EFFECT OF INSTITUTIONAL CONTEXT ON THE GOVERNANCE OF EMERGENT SUPPLY CHAINS: A CASE STUDY OF CASSAVA SECTOR IN VIETNAM - Kien Trung Nguyen (Universitas Sebelas Maret, 2020)
This paper investigates how transactions between firms are organized in an emerging market and how supply network governance affects supply network outcomes and catching up with merging market firms. We explored firms’ choices of governance in a specific context of Vietnam, where a legal institution is characterized by a weak legal system for contractual enforcement and socio-economic institution is characterized by transition from central planning into the market mechanism. This study examines how firms in the cassava sector in Vietnam structure their transactions and how supply network governance relates to certain supply network outcomes. A comparative case study method was adopted in this research. Two cassava supply networks, of which one is traditional type and another is led by a foreign-invested firm, were selected for study. Our findings indicate that institutional context, supply chain structure, product characteristics, relationship investment influence firms’ choices of governance, and firms’ choices of governance affect supply chain network outcomes and local firms’ catching up. In the absence of legal enforcement, market governance is popularly applied in the supply chain with fragmented structure while relational governance is popular used in more concentrated supply network. Higher value creation and more possibilities for catching up but more inequality in income distribution in supply chain with large scale lead firm. Lower value creation, rare possibilities for catching up but more equality in income distribution in supply chain with fragmented small scale firms.